Engineering the Future of Outreach - Emily Dommermuth; Megan Welsh (Issues in Science and Technology Librarianship)
While academic libraries strive to meaningfully engage their campus communities, it can be hard to imagine new and creative outreach strategies. InfoMotion, a customized tricycle, is the University of Colorado Boulder Libraries’ “vehicle” to meet patrons where they are and embed ourselves in the campus community. InfoMotion was mobile and eye-catching, but it was cumbersome as we navigated campus pathways. The authors discuss their institutional context and describe an impactful partnership with engineering students to design an electric-assist system for InfoMotion. This collaboration resulted in a more user-friendly way for Libraries personnel to engage with the campus community, and helped the authors learn about student information needs while building relationships with engineering faculty and students.